Mobile android application development for anxiety and pain management: Usability and validity testing of audio hypno-spiritual therapy in ICU settings - Purnawan Iwan; Sutrisna Eman; Hidayat Arif Imam; Wirakhmi Ikit Netra (BIO Web of Conferences)
Anxiety and pain in patients with acute coronary syndrome (ACS) can worsen their condition and extend hospital stays. Conventional therapies, including hypnosis and spiritual support, are beneficial but often limited by time and staffing. This study aims to develop and validate a mobile-based Audio Hypno-Spiritual Therapy application, “Harmony,” to address these limitations. This research and development study used a prototype model. Validity was assessed by four experts in hypnosis, spirituality, critical care nursing, and cardiovascular disease, chosen for their expertise in relevant fields, using Aiken’s V analysis. Usability testing with eight ICCU patients evaluated the application’s practicality and effectiveness. The Harmony app demonstrated strong validity with an Aiken’s V value of 0.86. Usability testing, conducted with the USE Questionnaire, produced satisfaction scores ranging from 5.06 to 5.75 out of 7, indicating positive user experience and high satisfaction. The Harmony application shows high validity and usability, supporting its potential as a practical approach to reduce anxiety and pain in ACS patients in the ICCU. Future studies should include larger samples and evaluate the long-term impact of this intervention on patient outcomes.